A high-initial-efficiency, low-specific-surface-area asphalt-based hard carbon sodium-ion battery negative electrode material and a preparation method thereof

CN122212096BActive Publication Date: 2026-10-30DINGYUAN DONGCHANG CARBON-BASED MATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202610615739.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-05-07
Publication Date
2026-10-30
Estimated Expiration
2046-05-07

AI Technical Summary

Technical Problem

[0003]为解决上述问题,现有技术开展了诸多尝试,但均存在明显的局限性:部分技术采用KOH等强碱对沥青进行活化处理,虽能通过刻蚀作用调控孔结构、提高储钠容量,但强碱活化会进一步增大材料比表面积,加剧电解液分解,牺牲了首次库伦效率与循环稳定性,且活化后处理过程复杂,增加了产业化成本;部分技术通过添加酚醛树脂、环氧树脂等高分子聚合物对沥青进行共混改性,虽能调控碳材料的交联结构,减少熔融团聚,但引入的高分子树脂原料成本较高,大幅提升了硬碳材料的制备成本,违背了沥青前驱体低成本的核心优势;此外,常规沥青碳化工艺多采用单一速率升温,缺乏对热解过程中挥发分释放速率的有效控制,挥发分快速逸出易在碳基体中形成大量开孔和结构缺陷,不仅增加了副反应界面,还导致SEI膜反复破裂与重构,加速电池容量衰减

Benefits of technology

[0035]1. 本发明通过硼硅协同改性与梯度升温预氧化的联合调控,从源头上优化了沥青前驱体的热稳定性与交联结构,显著降低了硬碳材料的比表面积和孔缺陷。硼酸与正硅酸乙酯在沥青表面形成的B-O-C/Si-O-C交联网络,有效抑制了碳化过程中的熔融团聚与孔结构塌缩。分段保温预氧化使沥青逐步发生脱氢、氧化交联,既固定了颗粒形态,避免剧烈热解产生大量开孔,又适度引入含氧官能团助力形成闭孔结构。二者协同作用,使最终硬碳的BET比表面积控制在10m2/g以下,远低于常规沥青基硬碳,有效减少了电解液与材料本体的副反应界面,从体相结构层面奠定了电化学性能提升的基础。

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The application belongs to the technical field of sodium ion battery materials, and particularly relates to a high-initial-efficiency and low-specific-surface-area pitch-based hard carbon sodium ion battery negative electrode material and a preparation method thereof. The application realizes the optimization of the thermal stability and cross-linking structure of the pitch precursor from the source by the joint regulation of boron-silicon synergistic modification and gradient temperature pre-oxidation, and significantly reduces the specific surface area and pore defects of the hard carbon material. The primary hard carbon powder is subjected to organic-inorganic two-stage interface passivation, and the precise closure of the surface defects of the hard carbon is realized on the nanoscale, and the first coulomb efficiency is greatly improved. The hard carbon material prepared by the application has high reversible capacity, excellent rate performance and super-long cycle stability, and the comprehensive electrochemical performance is outstanding, thereby providing a feasible technical path for the industrialization of high-performance and low-cost sodium ion battery negative electrode materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of sodium-ion battery material technology, specifically relating to a high-efficiency, low-specific-surface-area pitch-based hard carbon sodium-ion battery anode material and its preparation method. Background Technology

[0002] Sodium-ion batteries have shown great potential in large-scale energy storage and low-speed electric vehicles due to their abundant resources and low cost. However, traditional graphite anodes have extremely low sodium storage capacity because the interlayer spacing is too small (~0.335nm), making it difficult to effectively embed the large-radius Na⁺ (1.02Å). Hard carbon materials, with their disordered stacked graphite-like microcrystalline structure, large interlayer spacing (>0.37nm), and abundant nanopores, have become the most promising sodium battery anode materials for industrialization.

[0003] To address the aforementioned issues, numerous attempts have been made in existing technologies, but all exhibit significant limitations: some technologies employ strong alkalis such as KOH to activate asphalt, which, while capable of regulating pore structure and increasing sodium storage capacity through etching, further increases the specific surface area of ​​the material, exacerbates electrolyte decomposition, sacrifices initial coulombic efficiency and cycle stability, and the post-activation treatment process is complex, increasing industrialization costs; some technologies modify asphalt by adding polymers such as phenolic resins and epoxy resins, which can regulate the crosslinking structure of carbon materials and reduce melt agglomeration, but the introduced polymeric resin raw materials are expensive, significantly increasing the preparation cost of hard carbon materials, contradicting the core advantage of low-cost asphalt precursors; furthermore, conventional asphalt carbonization processes often employ a single rate of heating, lacking effective control over the release rate of volatiles during pyrolysis. Rapid escape of volatiles easily forms numerous open pores and structural defects in the carbon matrix, not only increasing the number of side reaction interfaces but also causing repeated rupture and reconstruction of the SEI film, accelerating battery capacity decay.

[0004] Meanwhile, existing technologies for passivating hard carbon surfaces mostly employ a single organic coating or inorganic modification method. A single passivation method is difficult to achieve precise and complete sealing of surface defects: although organic coating can fill some micropores, active sites will still remain on the surface of the organic layer, which cannot completely inhibit electrolyte decomposition; inorganic passivation alone is prone to forming a continuous inorganic layer, which hinders the rapid transport of sodium ions and reduces the rate performance of the material.

[0005] Therefore, there is an urgent need to develop a new method for preparing pitch-based hard carbon anode materials that is simple in process, cost-controllable, and can simultaneously achieve high reversible capacity, high first-efficiency and excellent cycle performance. Summary of the Invention

[0006] The purpose of this invention is to address existing problems by providing a high-efficiency, low-specific-surface-area pitch-based hard carbon sodium-ion battery anode material and its preparation method.

[0007] This invention is achieved through the following technical solution:

[0008] A method for preparing a high-efficiency, low-specific-surface-area pitch-based hard carbon sodium-ion battery anode material includes the following steps:

[0009] S1, Borosilicate synergistic modification:

[0010] Asphalt powder was mixed with a modifying liquid, stirred and adsorbed under sealed and dry conditions, and dried to obtain borosilicate synergistic modified asphalt powder.

[0011] S2, Gradient temperature pre-oxidation:

[0012] Borosilicate-modified asphalt powder was subjected to gradient heating pre-oxidation treatment in a humidity-controlled oxygen-containing atmosphere to obtain pre-oxidized asphalt powder.

[0013] S3, Precise Temperature Controlled Carbonization:

[0014] Pre-oxidized asphalt powder is subjected to multi-stage temperature-controlled carbonization under an inert atmosphere to obtain primary hard carbon powder.

[0015] S4, Organic-Inorganic Bi-level Interface Passivation:

[0016] Organic ultrathin coating treatment is applied to primary hard carbon powder to form an ultrathin amorphous carbon layer with a thickness of <3nm;

[0017] Organically coated hard carbon powder is contacted with an extremely dilute solution containing silicon or boron sources, and after drying and heat treatment, an inorganic oxide passivation layer with island-like distribution and a surface coverage of 10-30% is formed on the surface.

[0018] S5. Post-processing:

[0019] Hard carbon powder with a two-stage interface passivation was ball-milled and sieved to obtain pitch-based hard carbon sodium-ion battery anode material.

[0020] Further, the asphalt powder mentioned in step S1 is: petroleum asphalt or coal tar pitch with a softening point of 80~150℃ is pulverized into powder with a particle size ≤100μm.

[0021] Further, the modified liquid in step S1 is prepared by weighing boric acid and tetraethyl orthosilicate according to a total modification amount of 0.5~2.0wt% and a B:Si mass ratio of (1~2):1, and dissolving them in anhydrous ethanol to form a modified liquid.

[0022] Furthermore, in step S1, the temperature is controlled at 60~80℃ and the stirring time is 2~4h during the stirring adsorption process;

[0023] The drying temperature is controlled at 80~85℃, the vacuum degree is ≤-0.09MPa, and the drying time is 6~12h.

[0024] The modified asphalt powder was stored under N2 protection and ambient humidity ≤30% RH conditions, and then subjected to subsequent pre-oxidation treatment within 12 hours.

[0025] Further, the specific operation of the gradient heating pre-oxidation treatment in step S2 is as follows: the borosilicate synergistic modified asphalt powder is spread with a layer thickness of ≤5mm, placed in an oxygen-containing atmosphere furnace with a desiccant added to the air inlet, and heated to 200~300℃ at a heating rate of 0.5~2℃ / min. During the heating process, constant temperature holding is performed in 2~3 segments, with a total holding time of 2~4h. The segmented holding includes holding at least 2~3 points from the three temperature points of 220℃, 250℃, and 280℃, with a holding time of 0.5~1.5h at each temperature point.

[0026] The desiccant is a type 4A molecular sieve.

[0027] Furthermore, the oxygen-containing atmosphere is air or a mixture of gases with an oxygen content of 5-20 vol%.

[0028] Further, the multi-stage temperature-controlled carbonization operation described in step S3 is as follows: the pre-oxidized asphalt powder is filled into a covered crucible and placed in a high-purity Ar or N2 inert atmosphere with a water content of <50ppm. The gas flow rate is 50~200mL / min. First, the temperature is raised to 500~600℃ at 1~3℃ / min and held for 1~2h. Then, the temperature is raised to 1200~1400℃ at 1~2℃ / min and held for 2~5h. After natural cooling, primary hard carbon powder is obtained.

[0029] Further, the specific process of organic ultrathin coating in step S4 is as follows: primary hard carbon powder is added to an anhydrous ethanol solution containing 0.3~1.5wt% glucose or citric acid, stirred for 6~12h, vacuum dried at 60~70℃, and then heat-treated at 600~800℃ for 1~2h under Ar atmosphere to form an ultrathin amorphous carbon layer with a thickness of <3nm.

[0030] Further, the formation process of the inorganic oxide passivation layer in step S4 is as follows: using the same boric acid or tetraethyl orthosilicate as in step S1 as the inorganic source, dissolving it in anhydrous ethanol to prepare an extremely dilute impregnation solution with a mass concentration ≤0.5%; then adding the organically coated hard carbon powder to the impregnation solution, stirring for 3-5 hours, and then using rotary evaporation to uniformly adsorb the inorganic source, followed by heat treatment at 500-600℃ for 0.5 hours under an Ar atmosphere to form an island-shaped distribution of B2O3 or SiO2 inorganic phase with a size ≤5nm;

[0031] The rotary evaporation process parameters are 50~60℃ and 50~80rpm.

[0032] Furthermore, in step S5, the ball-to-material ratio of the ball mill is (5~10):1, the ball milling time is 1~2 hours, and anhydrous ethanol is used as the dispersion medium.

[0033] The material was sieved through a 200-mesh sieve.

[0034] The present invention has the following advantages over the prior art:

[0035] 1. This invention optimizes the thermal stability and cross-linking structure of asphalt precursors from the source through the combined regulation of borosilicate synergistic modification and gradient-heating pre-oxidation, significantly reducing the specific surface area and pore defects of hard carbon materials. The BOC / Si-OC cross-linking network formed by boric acid and tetraethyl orthosilicate on the asphalt surface effectively inhibits melt agglomeration and pore structure collapse during carbonization. Segmented heat preservation pre-oxidation causes the asphalt to gradually undergo dehydrogenation and oxidative cross-linking, which not only fixes the particle morphology and avoids the generation of a large number of open pores by violent pyrolysis, but also moderately introduces oxygen-containing functional groups to help form a closed-pore structure. The synergistic effect of these two methods controls the BET specific surface area of ​​the final hard carbon to 10m². 2 The concentration of 45 g / g is significantly lower than that of conventional asphalt-based hard carbon, effectively reducing the side reaction interface between the electrolyte and the material bulk, thus laying the foundation for improved electrochemical performance from the perspective of bulk structure.

[0036] 2. This invention employs an organic-inorganic bipolar passivation process for primary hard carbon powder, achieving precise sealing of surface defects at the nanoscale and significantly improving the first-passivation efficiency. First, an ultrathin amorphous carbon layer (<3 nm) uniformly covers the primary hard carbon surface, filling micropores and reducing direct electrolyte contact. Subsequently, island-like B₂O₃ or SiO₂ inorganic phases (≤5 nm in size) selectively passivate the residual active sites in the organic layer. However, their island-like distribution ensures that most of the surface remains a conductive carbon layer, without affecting sodium ion transport. This bipolar passivation mechanism effectively improves the first-passivation efficiency, showing a significant improvement compared to single passivation methods.

[0037] 3. The hard carbon material prepared by this invention possesses high reversible capacity, excellent rate performance, and ultra-long cycle stability, exhibiting outstanding comprehensive electrochemical performance. Thanks to the rational control of the bulk structure and effective interface passivation, the material achieves an initial coulombic efficiency of 91.2% at 0.1C, a capacity retention rate of 95.6% after 1000 cycles at 1C, and a capacity recovery rate of 99.1% at 5C. This fully demonstrates that the stable bulk porous structure provides sufficient sites for sodium ion storage, while the dense passivated interface ensures interfacial stability during long-term cycling; the two work synergistically to achieve a balance between high initial efficiency and long lifespan. This invention provides a practical and feasible technical path for the industrialization of high-performance, low-cost sodium-ion battery anode materials. Detailed Implementation

[0038] To further explain the present invention, the following specific embodiments are described.

[0039] Example 1

[0040] A method for preparing a high-efficiency, low-specific-surface-area pitch-based hard carbon sodium-ion battery anode material includes the following steps:

[0041] S1, Borosilicate synergistic modification:

[0042] Industrial-grade petroleum asphalt with a softening point of 110℃ is pulverized into powder with a particle size of 50μm.

[0043] Boric acid and tetraethyl orthosilicate were weighed with a total modification amount of 0.5 wt% and a B:Si mass ratio of 1:1, and dissolved in anhydrous ethanol to form a modification solution.

[0044] Asphalt powder and modified liquid were mixed and stirred for 2 hours under sealed and drying conditions at 60°C. Then, boron-silicon synergistic modified asphalt powder was obtained by drying at 80°C and vacuum degree -0.09MPa for 6 hours.

[0045] The modified asphalt powder was stored under N2 protection and 20% RH conditions, and then subjected to subsequent pre-oxidation treatment within 12 hours.

[0046] S2, Gradient temperature pre-oxidation:

[0047] The borosilicate-modified asphalt powder was spread into a 5mm thick layer and placed in an air atmosphere furnace with a desiccant (type 4A molecular sieve) added to the air inlet. The temperature was increased from room temperature to 220℃ at a rate of 2℃ / min and held at that temperature for 1 hour. The temperature was then increased to 250℃ at a rate of 2℃ / min and held at that temperature for 1 hour. The temperature was then increased to 280℃ at a rate of 2℃ / min and held at that temperature for 1 hour. The temperature was then increased to 300℃ at a rate of 2℃ / min and the temperature was stopped. The powder was then allowed to cool naturally to room temperature to obtain pre-oxidized asphalt powder.

[0048] S3, Precise Temperature Controlled Carbonization:

[0049] The pre-oxidized asphalt powder was filled in a covered crucible and placed in a high-purity N2 inert atmosphere with a water content of <50ppm and a gas flow rate of 50mL / min. The temperature was first increased to 500℃ at 1℃ / min and held for 1h, then increased to 1200℃ at 1℃ / min and held for 2h. After natural cooling, primary hard carbon powder was obtained.

[0050] S4, Organic-Inorganic Bi-level Interface Passivation:

[0051] S401. Primary hard carbon powder is added to an anhydrous ethanol solution containing 0.3wt% citric acid, stirred for 6 hours, dried under vacuum at 60°C, and then heat-treated at 600°C for 1 hour under Ar atmosphere to form an ultrathin amorphous carbon layer with a thickness of <3nm.

[0052] S402. Using the same tetraethyl orthosilicate as in step S1 as the inorganic source, dissolve it in anhydrous ethanol to prepare an extremely dilute impregnation solution with a mass concentration of 0.5%; then add the organically coated hard carbon powder to the impregnation solution, stir for 3 hours, and then rotary evaporate at 50°C and 50 rpm to uniformly adsorb the inorganic source. Then heat-treat at 500°C for 0.5 hours under Ar atmosphere to form an island-shaped SiO2 inorganic phase with a size ≤5nm.

[0053] S5. Post-processing:

[0054] Hard carbon powder with a two-stage interface passivation was ball-milled at a ball-to-material ratio of 5:1 for 1 hour, using anhydrous ethanol as the dispersion medium.

[0055] After ball milling, the asphalt-based hard carbon sodium-ion battery anode material was obtained by passing it through a 200-mesh sieve.

[0056] Example 2

[0057] A method for preparing a high-efficiency, low-specific-surface-area pitch-based hard carbon sodium-ion battery anode material includes the following steps:

[0058] S1, Borosilicate synergistic modification:

[0059] Industrial-grade petroleum asphalt with a softening point of 110℃ is pulverized into powder with a particle size of 50μm.

[0060] Boric acid and tetraethyl orthosilicate were weighed according to a total modification amount of 1.0 wt% and a B:Si mass ratio of 1.5:1, and dissolved in anhydrous ethanol to form a modification solution.

[0061] Asphalt powder and modified liquid were mixed and stirred for 3 hours under sealed and drying conditions at 70°C. Then, boron-silicon synergistic modified asphalt powder was obtained by drying at 83°C and vacuum degree -0.09MPa for 9 hours.

[0062] The modified asphalt powder was stored under N2 protection and 20% RH conditions, and then subjected to subsequent pre-oxidation treatment within 12 hours.

[0063] S2, Gradient temperature pre-oxidation:

[0064] The borosilicate-modified asphalt powder was spread into a 5mm thick layer and placed in an air atmosphere furnace with a desiccant (type 4A molecular sieve) added to the air inlet. The temperature was increased from room temperature to 220℃ at a rate of 2℃ / min and held at that temperature for 0.5h. The temperature was then increased to 250℃ at a rate of 2℃ / min and held at that temperature for 1.5h. The temperature was then increased to 280℃ at a rate of 2℃ / min and held at that temperature for 1h. The temperature was then increased to 300℃ at a rate of 2℃ / min and the heating was stopped. The powder was then allowed to cool naturally to room temperature to obtain pre-oxidized asphalt powder.

[0065] S3, Precise Temperature Controlled Carbonization:

[0066] The pre-oxidized asphalt powder was loaded into a covered crucible and placed in a high-purity Ar inert atmosphere with a water content of <50ppm. The gas flow rate was 100mL / min. The temperature was first raised to 550℃ at 2℃ / min and held for 1.5h, then raised to 1300℃ at 1.5℃ / min and held for 4h. After natural cooling, primary hard carbon powder was obtained.

[0067] S4, Organic-Inorganic Bi-level Interface Passivation:

[0068] S401. Primary hard carbon powder is added to an anhydrous ethanol solution containing 1 wt% citric acid, stirred for 9 h, dried under vacuum at 65 °C, and then heat-treated at 700 °C for 1.5 h under Ar atmosphere to form an ultrathin amorphous carbon layer with a thickness of <3 nm.

[0069] S402. Using the same tetraethyl orthosilicate as in step S1 as the inorganic source, dissolve it in anhydrous ethanol to prepare an extremely dilute impregnation solution with a mass concentration of 0.5%; then add the organically coated hard carbon powder to the impregnation solution, stir for 4 hours, and then rotary evaporate at 55°C and 60 rpm to uniformly adsorb the inorganic source. Then heat-treat at 550°C for 0.5 hours under Ar atmosphere to form an island-shaped SiO2 inorganic phase with a size ≤5nm.

[0070] S5. Post-processing:

[0071] Hard carbon powder with a two-stage interface passivation was ball-milled at a ball-to-material ratio of 8:1 for 1.5 hours, using anhydrous ethanol as the dispersion medium.

[0072] After ball milling, the asphalt-based hard carbon sodium-ion battery anode material was obtained by passing it through a 200-mesh sieve.

[0073] Example 3

[0074] A method for preparing a high-efficiency, low-specific-surface-area pitch-based hard carbon sodium-ion battery anode material includes the following steps:

[0075] S1, Borosilicate synergistic modification:

[0076] Industrial-grade petroleum asphalt with a softening point of 110℃ is pulverized into powder with a particle size of 50μm.

[0077] Boric acid and tetraethyl orthosilicate were weighed according to a total modification amount of 2.0 wt% and a B:Si mass ratio of 2:1, and dissolved in anhydrous ethanol to form a modification solution.

[0078] Asphalt powder was mixed with the modification liquid and stirred and adsorbed at 80°C for 4 hours under sealed and drying conditions. Then, it was dried at 85°C under a vacuum of -0.09 MPa for 12 hours to obtain boron-silicon synergistic modified asphalt powder.

[0079] The modified asphalt powder was stored under N2 protection and 20% RH conditions, and then subjected to subsequent pre-oxidation treatment within 12 hours.

[0080] S2, Gradient temperature pre-oxidation:

[0081] The borosilicate-modified asphalt powder was spread in a layer with a thickness of 5 mm and placed in an air atmosphere furnace with a desiccant (the desiccant being a type 4A molecular sieve) added to the air inlet. The temperature was increased from room temperature to 250°C at a rate of 2°C / min and held at that temperature for 1.2 h. The temperature was then increased to 280°C at a rate of 2°C / min and held at that temperature for 1.8 h. The temperature was then increased to 300°C at a rate of 2°C / min. The heating was then stopped and the powder was allowed to cool naturally to room temperature to obtain pre-oxidized asphalt powder.

[0082] S3, Precise Temperature Controlled Carbonization:

[0083] The pre-oxidized asphalt powder was filled in a covered crucible and placed in a high-purity N2 inert atmosphere with a water content of <50ppm and a gas flow rate of 200mL / min. The temperature was first raised to 600℃ at 3℃ / min and held for 2h, then raised to 1400℃ at 2℃ / min and held for 5h. After natural cooling, primary hard carbon powder was obtained.

[0084] S4, Organic-Inorganic Bi-level Interface Passivation:

[0085] S401. Primary hard carbon powder is added to an anhydrous ethanol solution containing 1.5 wt% glucose, stirred for 12 h, dried under vacuum at 70 °C, and then heat-treated at 800 °C for 2 h under Ar atmosphere to form an ultrathin amorphous carbon layer with a thickness of <3 nm.

[0086] S402. Using the same tetraethyl orthosilicate as in step S1 as the inorganic source, dissolve it in anhydrous ethanol to prepare an extremely dilute impregnation solution with a mass concentration of 0.5%; then add the organically coated hard carbon powder to the impregnation solution, stir for 5 hours, and then rotary evaporate at 60°C and 80 rpm to uniformly adsorb the inorganic source. Then heat-treat at 600°C for 0.5 hours under Ar atmosphere to form an island-shaped SiO2 inorganic phase with a size ≤5nm.

[0087] S5. Post-processing:

[0088] Hard carbon powder with a two-stage interface passivation was ball-milled at a ball-to-material ratio of 10:1 for 2 hours, using anhydrous ethanol as the dispersion medium.

[0089] After ball milling, the asphalt-based hard carbon sodium-ion battery anode material was obtained by passing it through a 200-mesh sieve.

[0090] Comparative Example 1

[0091] Compared with Example 2, Comparative Example 1 omits the borosilicate modification in step S1, while the other steps and parameters are the same as in Example 2.

[0092] Comparative Example 2

[0093] Compared with Example 2, Comparative Example 2 omits the pre-oxidation treatment in step S2, while the other steps and parameters are the same as in Example 2.

[0094] Comparative Example 3

[0095] Compared with Example 2, Comparative Example 3 omits the borosilicate modification in step S1 and the pre-oxidation treatment in step S2, and directly carbonizes the sample. The other steps and parameters are the same as in Example 2.

[0096] Comparative Example 4

[0097] Compared with Example 2, in Comparative Example 4, only the primary organic coating is performed in step S4, and the secondary inorganic passivation is omitted. The other steps and parameters are the same as in Example 2.

[0098] Comparative Example 5

[0099] Compared with Example 2, in Comparative Example 5, only inorganic passivation treatment is performed in step S4, and the first-level organic coating treatment is omitted. The other steps and parameters are the same as in Example 2.

[0100] 1. Performance Testing

[0101] 1.1 Physicochemical Performance Testing

[0102] The Brunauer-Emmett-Teller (BET) method was used to test the N2 adsorption isotherm of the material using a nitrogen adsorption-desorption apparatus, and the BET specific surface area was calculated. Before the test, the sample was degassed under vacuum at 120℃ for 12 hours.

[0103] The mesopore size and pore volume of the material were calculated using the Barrett-Joyner-Halenda (BJH) method, and the pore structure distribution characteristics were analyzed.

[0104] 1.2 Electrochemical performance testing

[0105] 1.2.1 Electrode preparation:

[0106] Hard carbon material (active material), conductive carbon black, and sodium carboxymethyl cellulose were mixed in a mass ratio of 8:1:1, and deionized water was added to prepare a slurry. This slurry was then uniformly coated onto a copper foil current collector. After vacuum drying at 60℃ for 12 hours, the slurry was punched into φ12mm electrode sheets. The active material loading of the electrode sheets was 1.0~1.2mg / cm³. 2 .

[0107] 1.2.2 Button cell assembly:

[0108] CR coin cells were assembled in an argon-atmospheric glove box (H2O < 0.1 ppm, O2 < 0.1 ppm), using a sodium metal sheet as the counter electrode and glass fiber as the separator. The electrolyte was 1 mol / L NaClO4 dissolved in ethylene carbonate and dimethyl carbonate (volume ratio 1:1). 5% fluoroethylene carbonate was added as a film-forming additive.

[0109] 1.2.3 Electrochemical Testing

[0110] Initial Coulombic Efficiency (ICE) and Charge / Discharge Capacity: Using the Blue Battery Test System, constant current charge / discharge tests were conducted at a current density of 0.1C within the voltage range of 0.01~2.0V. The initial discharge capacity and initial charge capacity were recorded, and the initial coulombic efficiency was calculated.

[0111] Cyclic performance: The capacity retention rate was tested after 1000 cycles of constant current charge-discharge cycling at a current density of 1C within the voltage range of 0.01~2.0V.

[0112] Rate performance: Charge and discharge at current densities of 0.1C, 0.2C, 0.5C, 1C, 2C, and 5C in the voltage range of 0.01~2.0V, record the discharge specific capacity at different rates, and test the capacity recovery rate after recovering from 5C rate to 0.1C.

[0113] 2. Test Results

[0114] Table 1. Physicochemical properties of materials from Examples 1-3 and Comparative Examples 1-5

[0115] Example 1 8.2 0.021 Example 2 6.5 0.017 Example 3 7.8 0.020 Comparative Example 1 15.6 0.038 Comparative Example 2 11.8 0.031 Comparative Example 3 32.8 0.085 Comparative Example 4 9.5 0.025 Comparative Example 5 11.2 0.029

[0116] Table 2 Electrochemical performance indicators of materials in Examples 1-3 and Comparative Examples 1-5

[0117] Example 1 88.5 92.1 98.3 Example 2 91.2 95.6 99.1 Example 3 89.8 93.5 98.7 Comparative Example 1 82.6 81.3 92.5 Comparative Example 2 84.8 84.6 94.2 Comparative Example 3 71.5 62.8 85.3 Comparative Example 4 85.3 86.8 95.2 Comparative Example 5 83.1 82.5 93.1

[0118] As can be seen from the data in Tables 1 and 2 above, this invention successfully prepared a pitch-based hard carbon anode material with both low specific surface area and high initial coulombic efficiency through the synergistic effect of four core processes.

[0119] Compared to Example 2, Comparative Example 2, after omitting step S1 modification, had a specific surface area that increased from 6.5 m². 2 / g increased to 15.6m 2 / g, the initial coulombic efficiency decreased from 91.2% to 82.6%, indicating that the BOC / Si-OC crosslinking network formed by boric acid and tetraethyl orthosilicate on the asphalt surface inhibited melt agglomeration and pore structure collapse during carbonization, reduced the number of open pores, and thus reduced the specific surface area.

[0120] In Comparative Example 2, after omitting step S2 pre-oxidation, the specific surface area increased to 11.8 m². 2 / g indicates that the segmented heat preservation and pre-oxidation process causes the asphalt to gradually undergo dehydrogenation and oxidative cross-linking, which fixes the particle shape, avoids the generation of a large number of open pores during carbonization due to violent pyrolysis, and at the same time, the moderate introduction of oxygen-containing functional groups helps to form a closed-cell structure.

[0121] Comparative Example 3, by omitting both S1 and S2, achieves a material specific surface area as high as 32.8 m². 2 / g, ICE is only 71.5%, and the capacity retention rate after 1000 cycles is only 62.8%, indicating that direct carbonization of unmodified and pre-oxidized asphalt will produce a large number of open channels and surface defects, leading to continuous decomposition of the electrolyte and easy rapid decay.

[0122] Comparative Example 4 only has organic coating, with a specific surface area of ​​9.5 m². 2 / g, ICE is 85.3%, Comparative Example 5 only has inorganic passivation, specific surface area is 11.2m² 2 / g, ICE is 83.1%. The ultrathin amorphous carbon layer fills the surface micropores, reducing the direct contact between the electrolyte and the hard carbon matrix; the island-shaped inorganic oxide further passivates the residual active defect sites in the organic layer, but its island-shaped distribution ensures that most of the surface remains a conductive carbon layer, without affecting sodium ion transport. The synergistic effect of these two factors significantly reduces irreversible capacity while maintaining excellent rate performance.

[0123] The specific embodiments described above further illustrate the purpose, technical solution, and beneficial effects of the present invention. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A method for preparing a high-efficiency, low-specific-surface-area pitch-based hard carbon sodium-ion battery anode material, characterized in that, Includes the following steps: S1, Borosilicate synergistic modification: Asphalt powder was mixed with a modifying liquid, stirred and adsorbed under sealed and dry conditions, and dried to obtain borosilicate synergistic modified asphalt powder. The asphalt powder is made by crushing petroleum asphalt or coal tar pitch with a softening point of 80~150℃ into powder with a particle size ≤100μm. The modified liquid is prepared by weighing boric acid and tetraethyl orthosilicate with a total modification amount of 0.5~2.0wt% and a B:Si mass ratio of (1~2):1, and dissolving them in anhydrous ethanol to form the modified liquid. The temperature is controlled at 60~80℃ and the stirring time is 2~4h during the stirring adsorption process; The drying temperature is controlled at 80~85℃, the vacuum degree is ≤-0.09MPa, and the drying time is 6~12h; The modified asphalt powder was stored under N2 protection and ambient humidity ≤30% RH conditions, and then subjected to subsequent pre-oxidation treatment within 12 hours. S2, Gradient temperature pre-oxidation: Borosilicate-modified asphalt powder was subjected to gradient heating pre-oxidation treatment in a humidity-controlled oxygen-containing atmosphere to obtain pre-oxidized asphalt powder. The specific operation of the gradient heating pre-oxidation treatment is as follows: the borosilicate synergistic modified asphalt powder is spread with a layer thickness of ≤5mm, placed in an oxygen-containing atmosphere furnace with a desiccant added to the air inlet, and heated to 200~300℃ at a heating rate of 0.5~2℃ / min. During the heating process, constant temperature holding is carried out in 2~3 sections, with a total holding time of 2~4h. The section holding includes holding at least 2~3 points from the three temperature points of 220℃, 250℃, and 280℃, with a holding time of 0.5~1.5h at each temperature point. S3, Precise Temperature Controlled Carbonization: Pre-oxidized asphalt powder is subjected to multi-stage temperature-controlled carbonization under an inert atmosphere to obtain primary hard carbon powder. The specific operation of the multi-stage temperature-controlled carbonization is as follows: the pre-oxidized asphalt powder is filled into a covered crucible and placed in a high-purity Ar or N2 inert atmosphere with a water content of <50ppm. The gas flow rate is 50~200mL / min. First, the temperature is raised to 500~600℃ at 1~3℃ / min and held for 1~2h. Then, the temperature is raised to 1200~1400℃ at 1~2℃ / min and held for 2~5h. After natural cooling, primary hard carbon powder is obtained. S4, Organic-Inorganic Bi-level Interface Passivation: Organic ultrathin coating treatment is applied to primary hard carbon powder to form an ultrathin amorphous carbon layer with a thickness of <3nm; Organically coated hard carbon powder is contacted with an extremely dilute solution containing silicon or boron sources, and after drying and heat treatment, an inorganic oxide passivation layer with island-like distribution and a surface coverage of 10-30% is formed on the surface. The specific process of the organic ultrathin coating is as follows: primary hard carbon powder is added to an anhydrous ethanol solution containing 0.3~1.5wt% glucose or citric acid, stirred for 6~12h, vacuum dried at 60~70℃, and then heat-treated at 600~800℃ for 1~2h under Ar atmosphere to form an ultrathin amorphous carbon layer with a thickness of <3nm. The formation process of the inorganic oxide passivation layer is as follows: using boric acid or tetraethyl orthosilicate as the same as in step S1 as the inorganic source, dissolving it in anhydrous ethanol to prepare an extremely dilute impregnation solution with a mass concentration ≤0.5%; then adding the organically coated hard carbon powder to the impregnation solution, stirring for 3-5 hours, and then using rotary evaporation to uniformly adsorb the inorganic source; then heat-treating at 500-600℃ for 0.5 hours under an Ar atmosphere to form an island-shaped distribution of B2O3 or SiO2 inorganic phase with a size ≤5nm; The process parameters for rotary evaporation are 50~60℃ and 50~80rpm. S5. Post-processing: The hard carbon powder with dual-level interface passivation was ball-milled and sieved to obtain pitch-based hard carbon sodium-ion battery anode material. The ball milling process involves a ball-to-material ratio of (5~10):1, a milling time of 1~2 hours, and anhydrous ethanol as the dispersion medium. The material was sieved through a 200-mesh sieve.

2. The preparation method according to claim 1, characterized in that, The oxygen-containing atmosphere is air or a mixture of gases with an oxygen content of 5-20 vol%.

Citation Information

Patent Citations

  • Stannum and carbon composite nano-fiber film negative-electrode material and preparation method thereof

    CN101626075A

  • Process for the polymerization of polymerizable hydrocarbons

    DE1177343B